Jo bhi aap chahein - Sharma, Seema; Sharma, M. L. (New Delhi : Sanjeev, 2021)
A love story and sacrifices of two sisters for each other, also game of capturing kingdom from elder brother by younger- well written by Shakespeare with interesting and laughing incidents. Name of this play was decided by people's opinion.
Keywords: Shakespeare